2017
DOI: 10.4172/2161-1459.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-arthritis Activity of Flavonoids Fractions Isolated from Centipeda minima Leaves Extracts in Rats

Abstract: Centipeda minima has been used since centuries as a traditional medicinal plant in treating a number of disease conditions, the bioactive components responsible for its anti-inflammatory and anti-arthritis activity have not been identified. The present study was planned to isolate flavonoids fractions from Centipeda minima leaves extracts, and assessed anti-inflammatory and anti-arthritis activity in rats. The hydroalcoholic and aqueous extracts of Centipeda minima leaves were prepared and evaluated for in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The chemicals extracted from Centipeda minima containing poly phenols and flavonoids compound and these organic substances impart important role in anti-inflammatory and anti-arthritic activity. 31…”
Section: Anti-inflammatory and Anti-arthritic Activitymentioning
confidence: 99%
“…The chemicals extracted from Centipeda minima containing poly phenols and flavonoids compound and these organic substances impart important role in anti-inflammatory and anti-arthritic activity. 31…”
Section: Anti-inflammatory and Anti-arthritic Activitymentioning
confidence: 99%
“…The use of the whole plant in Chinese folk medicine for treating cold, nasal allergy, diarrhea, malaria and asthma has a long history [2]. Previous pharmacological studies have demonstrated that extracts of Centipeda minima and some isolated compounds from the Centipeda minima possess anti-tumor [3,4], anti-proliferative [5,6], antioxidant and anti-inflammatory [7,8] properties. Phytochemical investigation of this herbal material has led to the identification of various compounds such as sesquiterpene lactones, triterpenes, flavonoids, polyphenol, phenolic and organic acid [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The plant of Centipeda minima is used commonly as a traditional Chinese medicine for treating colds, nasal allergy, cough, asthma, headaches, nasopharyngeal carcinoma, and swellings. Earlier phytochemical investigations of Centipeda minima revealed the presence of sesquiterpene lactones, triterpenoids, terpenoid glycosides, phenolic acids, and flavones . Prior studies have demonstrated that Centipeda minima has multiple biological effects, for example, antitumor, ,, antiproliferative, neuroprotective, antiarthritis, , antibacterial, , antioxidant, and anti-inflammatory activities …”
mentioning
confidence: 99%